PEMANFAATAN SISTEM INFORMASI APLIKASI ONLINE PUBLIC ACCESS CATALOGUE (OPAC) PADA PERPUSTAKAAN IAIN BATUSANGKAR - Armizawati Armizawati (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2017)
In this qualitative case study, we examined benefit Online Public Acsses Catalogue (OPAC) in IAIN Library. This research focus to student that use Online Public Access Catalogue (OPAC). This research using Miles & Hubberman model (Reduction data, show data and conclusion). Data were collected purposive sampling through observation and interview. The findings, showed that Online Public Acsses Catalogue (OPAC) give benefit,effective and efisien use to find all book fast.